Pandemia da COVID-19: influência no desenvolvimento da criança na primeira infância - Diógenes, Mariana da Silva (2023)
COVID-19 spread rapidly throughout the world and to contain the high number of people infected by SARS-CoV-2, restrictive measures were adopted, such as social isolation. In this context, thousands of children found themselves exposed to multiple stressors with the potential to compromise healthy child development. The objective was to evaluate the influence of the COVID-19 pandemic on children's development in early childhood. Cross-sectional study, carried out in the state of Ceará, with 306 children aged five to 66 months. Data collection took place from August 2021 to May 2022 through Google Forms, containing the Questionnaire on sociodemographic and clinical data of the child and parents/guardians and the Ages and Stages Questionnaires 3rd Edition (ASQ-3) in the Brazilian version, depending on the child's age. 18 ASQ-3 questionnaires were used, which contain 30 questions divided into five development domains: communication, gross motor coordination, fine motor coordination, problem solving and personal/social. The questionnaires have a pre-defined cutoff score for each domain, classified as: above, close to and below the cutoff point. The data were analyzed in the Statistical Package for the Social Sciences (SPSS) version 20.0, using descriptive and inferential statistics, using Pearson's Chi-Square and Likelihood Ratio tests to evaluate the association between predictor variables and outcome. Analyzes with p<0.05 were considered statistically significant. As a result, the majority of children were 24 to 60 months old (63.7%), female (50.3%), non-white (59.3%); born at term (88.5%); no indication for hospitalization (85.6%); exclusively breastfeeding until six months of age (58.2%); not exposed to risk of violence (91.1%) and without previous comorbidities (74.8%). In the analysis of child development, the problem solving and motor coordination domains showed greater impairment, with statistical significance (p<0.05), in children cared for by guardians with education up to high school, who had access to financial aid programs from the Government and who have a monthly family income of up to three minimum wages. The communication, fine motor and personal/social coordination domains showed greater impairment in development in children who did not have social contact with friends, did not perform physical activity or did not have the opportunity for weekly leisure time during the pandemic period. The personal/social domain showed greater impairment in children who increased their use of screens during the pandemic and in children who did not have remote classes and did not show changes in school performance. It is concluded that although the majority of children present adequate development, some sociodemographic, social, clinical and school characteristics influenced healthy child development.